Surgical adhesives - Thomazini-santos, I. A. [UNESP]; Barraviera, S. R. C. S. [UNESP]; Mendes-giannini, M. J. S. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2001)
The authors have performed a literature review of surgical adhesives, such as cyanoacrylate, collagen gelatin, and fibrin glue. They have included different types of commercial and non-commercial fibrin sealants and have reported on the different components in these adhesives, such as fibrinogen, cryoprecipitate, bovine thrombin, and thrombin-like fraction of snake venom.
Keywords: fibrin glue; surgical adhesives; collagen gelatin; cyanoacrylates; fibrinogen; cryoprecipitate; bovine thrombin; thrombin-like fraction; snake venom